The Impact of Infectious Diseases on Athletes: Diagnosis, Management, and Return-To-Play Guidelines - May SALEM; Mohammad MOHAMMED (American Journal of Biomedicine and Pharmacy, 2025)
Orthopedic injuries are commonly associated with sports; however, infectious diseases also contribute significantly to morbidity among athletes. While moderate-intensity exercise enhances immune function, extreme exercise durations and intensities may suppress immunity. Respiratory infections are the most prevalent, although athletes are also susceptible to skin, bloodborne, sexually transmitted, and cardiac infections. Infectious disease outbreaks remain a persistent concern in athletic populations. The management of infections in athletes aligns with general medical treatment protocols, yet considerations regarding return-to-play decisions and infection prevention strategies are particularly important in this demographic.